ASSEMBLAGE OF NECTARIVOROUS BIRDS AND THEIR FLORAL RESOURCES IN AN ELFIN FOREST OF THE CENTRAL ANDES OF PERU - Gonzalez, Oscar (2019)
Nectarivorous birds (hummingbirds, flowerpiercers, and conebills) and their floral resources in an elfin forest of the central Andes of Peru (Unchog, Carpish Mountains) are described. This forest is well-known for its concentration of endemic species, mainly birds. We recorded the nectarivorous birds, vascular plants and the interactions among them between 2011-2014. The birds were recorded by direct observations and mist nets. Plants were evaluated with Gentry plots and occasional collection. A total of 26 nectarivorous bird species have been reported in this forest, however from our observations we detected from this assemblage 17 bird species that feed in plants’ nectar. A total of 27 plant species were visited by the birds. The nectarivorous birds were hummingbirds (Trochilidae, 12 species), flowerpiercers (Thraupidae, 4 species) and a conebill (Thraupidae: 1 specie). The plants were from 16 families and 14 orders. One species of hummingbird, Metallura theresiae, is endemic to Peru. On plants, Greigia macbrideana, Puya pseudoeryngioides, Centropogon isabellinus, Miconia alpina and Brachyotum lutescens are endemic to Peru. We comment on the species reported in previous expeditions and in the current checklists. Since this forest is important for its large number of endemic species, we comment on its current threats and the importance of accounting for ecological interactions to conserve montane forests.